Evaluating automated goals for home care support. Issue 2 (20th June 2016) - Clark, Julia S; Turner, Kenneth J.
Abstract : Purpose: – The purpose of this paper is to evaluate an approach to automating goals for supporting home care, with a view to understanding user experience when defining such goals and hence identifying improvements that could be made to the approach. Design/methodology/approach: – The study was designed to answer the key research question of whether users can understand, formulate and relate to automated goals for home care. In order to do this, a fictional text-based scenario was used about a couple with care needs. This helped to explore the feasibility, acceptability and usability of goals to manage care at home. Face-to-face qualitative interviews were undertaken with ten participants with a background in social care: four social care professionals; one health care professional; one formal carer; one informal carer; and three end users. Findings: – Overall, participants were positive about being able to control the MATCH (Mobilising Advanced Technologies for Care at Home) system through the use of goals. The results from the participant interviews will be used to help guide potential improvements to the home care system. The main issue that emerged from the study is that it would be valuable to think in terms of outcomes as a higher level than goals. A second consideration is that it would be desirable to adopt terminology that can be understood by all stakeholders. Research limitations/implications: – The study has demonstrated that automated goals for home care have a useful role to play and can be successfully used by end users and carers. Although the range of participants in the study was limited, it has allowed confidence to be built in the approach and has identified useful pointers for future development. Practical implications: – With the evaluation and validation of the goal-based approach, it has encouraged the developers to make automated goals more widely available in future deployment of the home care system. Social implications: – The use of automated goals to support home care has been shown to be acceptable to end users and carers. This will allow future home care systems to offer more personal and better customised services to those receiving telecare. Originality/value: – The study provides a unique evaluation of the use of automated goals to support home care. Previous use of goals in the literature has been for highly technical applications, so their application to home care is novel and speculative. The study has demonstrated that the approach is viable, useful, and usable by end users and carers.